Bidding for complex projects: Evidence from the acquisitions of IT services - Gian Luigi Albano; Federico Dini; Roberto Zampino (Fondazione Eni Enrico Mattei (FEEM), 2008)
Competitive bidding (as auctions) is commonly used to procure goods and services. Public buyers are often mandated by law to adopt competitive procedures to ensure transparency and promote full competition. Recent theoretical literature, however, suggests that open competition can perform poorly in allocating complex projects. In exploring the determinants of suppliers' bidding behavior in procurement auctions for complex IT services, we find results that are consistent with theory. We find that price and quality do not exhibit the classical tradeoff one would expect: quite surprisingly, high quality is associated to low prices. Furthermore, while quality is mainly driven by suppliers' experience, price is affected more by the scoring rule and by the level of expected competition. These results might suggest that (scoring) auctions fail to appropriately incorporate buyers' complex price/quality preferences in the tender design.
Keywords: D44; D86; H51; H57; 330; Procurement Auctions; Scoring Rules; IT Contracts; Price/Quality Ratio